Synergistic weak/strong coupling luminescence in Eu-metal-organic framework/Zn2GeO4:Mn2+ nanocomposites for ratiometric luminescence thermometer. (October 2018) - Zhang, Yuchi; Yao, Hanzhi; Xu, Yan; Xia, Zhiguo
Abstract: Engineering novel ratiometric temperature sensors with high temperature sensitivity is still of a great challenge in versatile temperature measurement fields. Herein, a self-calibrated optical luminescent thermometer based on Eu 3+ /Mn 2+ dual-activator was fabricated in the same nanocomposite system, which integrated the photoluminescence originated from the temperature-insensitive Eu-metal organic framework with weak coupling effect and the temperature-sensitive Zn2 GeO4 :Mn 2+ with strong coupling effect. Specifically, the as-prepared nanocomposites composed of lanthanide MOF Eu-BTC (BTC = 1, 3, 5-benzenetricarboxylic acid) and Zn2 GeO4 :Mn 2+ nanorods possessed Eu 3+ /Mn 2+ dual red/green emission, which displays excellent ratiometric temperature-sensing functions and also has high relative sensitivity ( S r ) of 4.1% ºC −1 when they are used as ratiometric luminescent thermometer in the physiological temperatures (25–45 °C). These results demonstrate that such a design strategy with synergistic weak/strong coupling luminescence is useful and the as-obtained Eu-MOF/Zn2 GeO4 :Mn 2+ nanocomposites can be potential for temperature sensor applications. Graphical abstract: We reported a Eu 3+ /Mn 2+ dual-activator luminescent thermometer composed of Eu-metal-organic framework and Zn2 GeO4 :Mn 2+ nanocomposites exhibiting excellent self-calibrated luminescent response towards temperature change. Highlights: A dual-activator Eu 3+ /Mn 2+ luminescent thermometer nanocomposite is designed. The self-calibrated luminescent response towards temperature is investigated. The as-prepared nanocomposite displays high temperature sensitivity.